The Effect of Total Quality Management and Supply Chain Management on Operational Performance (Study on UKM Sanan Tempe Chips Malang City) - Amalina, Rusvita Nur; Triningsih; Roz, Kenny (Universitas Muhammadiyah Malang, 2024)
This study aims to determine the effect of total quality management, and supply chain management on operational performance. This research was conducted on MSME owners of Sanan tempeh chips in Malang City with a total sample of 72 respondents. Data collection uses a questionnaire and a Likert scale to measure each item on the variable. The analytical method uses multiple linear regression analyses. The results of this study show that total quality management has no significant effect on operational performance, while supply chain management has a significant effect on operational performance. The simultaneous test proves that total quality management and supply chain management have a simultaneous effect on operational performance.